Comparison of the PACE 2 Assay, Two Amplification Assays, and Clearview EIA for Detection of Chlamydia trachomatis in Female Endocervical and Urine Specimens - Lauderdale, Tsai-Ling (American Society for Microbiology, 1999)
Screening for sexually transmitted diseases (STDs) in a greater proportion of sexually active patients has become an accepted protocol by most health care providers. The purpose of this study was to compare the current test methods for detection of Chlamydia trachomatis used at the University of South Alabama, the PACE 2 assay (Gen-Probe) and the Clearview EIA (Wampole Laboratories), with two amplification technologies, the AMP CT (Gen-Probe) and LCx (Abbott) assays. In addition, a number of demographic parameters were ascertained by asking questions at the time of examination as well as for health care provider concerns and preferences. One urine and four endocervical swab specimens were collected in random order from 787 female patients attending one of four obstetrics-gynecology clinics. Eighty-seven percent of patients had no STD-related symptoms. Patients were considered positive for C. trachomatis if three or more assays (swab and/or urine) were positive. Abbott and Gen-Probe confirmed discrepant results by alternate amplified assays. A total of 66 true-positive specimens were detected by use of the combination of endocervical swabs and urine specimens. After discrepant analysis, sensitivities for endocervical swab specimens for the EIA and the PACE 2, LCx, and AMP CT assays were 50, 81, 97, and 100%, respectively. Sensitivities for the LCx and AMP CT assays with urine specimens were 98 and 81%, respectively. The prevalence of C. trachomatis was 8.4%, as determined by amplification technology. Overall, the amplification technologies were the most sensitive methods with either swab (AMP CT assay) or urine (LCx assay) specimens. The PACE 2 assay offered the advantage of a simpler and less expensive assay with acceptable sensitivity. The clearview CT EIA, while yielding a rapid in-office result, had unacceptably low sensitivity. The wide variation in performance with amplification assays with urine specimens as reported in both this study and the literature obviates the need to clarify optimal parameters for this specimen type.